Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Konsumen pada Serab Coffee Brewery di Kota Depok - Putria Friska Nabila; Lady Diana Warpindyastuti; Dwi Puji Hastuti (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The rapid growth of the coffee shop industry creates intense competition, forcing business players to understand the factors influencing consumer purchasing decisions. This study aims to determine and analyze the effect of Price (X1) and Product Quality (X2) on Purchasing Decisions (Y) among consumers of Serab Coffee Brewery. Data collection was conducted by distributing structured questionnaires to 97 respondents determined using a non-probability sampling technique with a purposive sampling method. The collected primary data underwent instrument testing (validity and reliability), classical assumption testing, and were analyzed using multiple linear regression analysis via SPSS version 25. The test results indicate that both Price and Product Quality variables partially and simultaneously have a significant effect on Purchasing Decisions. Partially, the Price variable contributes an effect of 29.4%, while Product Quality contributes 27.4%. The Coefficient of Determination (R Square) value shows a figure of 0.568, indicating that the combined stimulus of price and product quality variables is able to explain 56.8% of the variation in the consumer Purchasing Decision variable, while the remaining 43.2% is influenced by other factors outside this study.